Long Term Effect of Residue Management, Nitrification and Urease Inhibitor on Non-target Soil Bacterial Community in Rice–Wheat and Maize–Wheat Cropping Systems - Chakraborty, Ranabir; Purakayastha, T. J.; Ramakrishnan, B.; Kour, Babanpreet; Bhowmik, Arpan; Das, Abinash (International Journal of Bio-resource and Stress Management, 2024)
An investigation was carried out from November, 2020 to April, 2021 at the Indian Agricultural Research Institute, New Delhi, employing a split-split plot layout with two cropping systems (rice-wheat and maize-wheat), four long-term crop residue management strategies including burning (CRB), removal (CRR), incorporation (CRI), and biochar (BC), and two nitrogen management: neem-coated urea (NCU) and Urea+dual (urease+nitrification) inhibitor (UUINI). Soil DNA was extracted and quantified for 16S bacteria, 16S archaea, nifH, ureC and anammox abundances using quantitative PCR. Additionally, Soil samples were analysed for available nitrogen (urea, NH4+, NO3-) and water-soluble carbon. Rice-wheat rotations favoured higher 16S bacterial abundance while maize-wheat elevated 16S archaea. Notably, CRI and BC exhibited higher bacterial abundance compared to CRR and CRB, while minimal impact was noticed for archaea. The nifH gene abundance was influenced by all treatments along with their interactions. UreC gene copies exhibited a direct relationship with 16S archaea and an inverse relationship with 16S bacteria; UUINI showed a higher abundance of ureC under CRI and BC in both cropping systems. Moreover, anammox abundance correlated positively with NH4+ and NO3- but negatively with unhydrolyzed urea, indicating the inhibitory effect of UUINI. These findings underscore the complex relationships among inhibitors, residue management, cropping systems and soil microbial communities, emphasizing the need for tailored approaches to optimise nutrient cycling and soil health in agricultural systems.